Elucidation of phosphate hydrolysis mechanism in water and in the elongation factor Tu (EF-Tu) - Ertem, Mehmed Zahid. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
The nature of phosphate hydrolysis reactions in solutions and in proteins is a topic that draws significant amount of interest due to the critical role of the phosphate hydrolysis reactions in the cellular activities. Studies on the phosphate hydrolysis reactions, directed towards the elucidation of the mechanism, created the main mechanistic debate on the phosphate hydrolysis reaction; whether it follows an associative or a dissociative pathway. This thesis is focused on two topics; the first one is the detailed investigation of the hydrolysis of methyl pyrophosphate trianion (CH3P2O7-3) and the second one is the analysis of the guanosine triphosphate (GTP) form of EF-Tu, a GTP hydrolyzing protein. Density Functional Theory (DFT) calculations were done for the investigation of the mechanism of the hydrolysis of methyl pyrophosphate trianion (CH3P2O7-3) and dissociative pathway was found to be favored over associative pathway for the hydrolysis reaction in aqueous medium. Moreover, the effect of the presence of the magnesium (Mg+2) ion on the hydrolysis of methyl pyrophosphate trianion was studied. In addition to these, the structural and dynamical properties of EFTu:GTP complex were analyzed by means of molecular dynamics (MD) simulations.
Keywords: Hydrolysis.; Phosphates.; Guanosine triphosphate.